Growth and pubertal development in adolescent male wrestlers - Piskin, I. E.; Gümüs, M.; Bayraktaroglu, T.; Akalin, T. C.; Yamaner, F. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Adolescence is a crucial period for linear growth, and sports training during this time may have positive or negative effects on some physiological processes as growth. The purpose of this study was to evaluate the effects of intense training during somatic growth on the onset of puberty and growth development in adolescent wrestlers. METHODS: Fifty adolescent male wrestlers and twenty-one sedentary healthy male controls aged between 13-15 years were selected. The wrestlers were from five different wrestling schools and were active at competitive level. The maturity status of the subjects and data about the anthropometric characteristics including age, body weight, height, and Body Mass Index (BMI) were evaluated. Serum testosterone, dehydroepiandrosterone sulphate, follicle stimulating hormone, luteinizing hormone, prolactin, cortisol, insulin like growth factor-1 (IGF-1), thyroid stimulating hormone (TSH) and free thyroxin were determined. RESULTS: Anthropometric characteristics and puberty levels according to the Tanner stage were similar in both groups. There were no significant differences between wrestlers and sedentary control groups in sex hormones, cortisol, IGF-1, prolactin levels (P>0.05) but TSH concentrations differed significantly (P=0.015). CONCLUSIONS: The results suggested that training in adolescent male wrestlers did not significantly change resting sex hormones or alter the onset of puberty as determined by assessment of pubertal stages. The wrestlers had lower body fat and greater energy expenditure per week, there were no significant differences in height, weight, or BMI.